RU486 Metabolite Inhibits CCN1/Cyr61 Secretion by MDA-MB-231-Endothelial Adhesion - Yu, Suhong; Yan, Cuicui; Wu, Wenjing; He, Sudan; Liu, Min; Liu, Jian; Yang, Xingtian; Ma, Ji; Lu, Yusheng; Jia, Lee (Frontiers in Pharmacology, 2019)
Successful adhesion of circulating tumor cells (CTCs) to microvascular endothelium of distant metastatic tissue is the key starting step of metastatic cascade that could be effectively chemoprevented as we demonstrated previously. Here we hypothesize that the hetero-adhesion may produce secretory biomarkers that may be important for both premetastatic diagnosis and chemoprevention. We show that co-incubation of triple-negative breast cancer (TNBC) cell line MDA-MB-231 with human pulmonary microvascular endothelial monolayers (HPMEC) secretes Cyr61 (CCN1), primarily from MDA-MB-231. However, addition of metapristone (RU486 metabolite) to the co-incubation system inhibits Cyr61 secretion probably via the Cyr61/integrin αvβ1 signaling pathway without significant cytotoxicity on both MDA-MB-231 and HPMEC. Transfection of MDA-MB-231 with Cyr61-related recombinant plasmid or siRNA enhances or reduces Cyr61 expression, accordingly. The transfection significantly changes hetero-adhesion and migration of MDA-MB-231, and the changed bioactivities by overexpressed CYR61 could be antagonized by metapristone in vitro. Moreover, the circulating MDA-MB-231 develops lung metastasis in mice, which could be effectively prevented by oral metapristone without significant toxicity. The present study, for the first time, demonstrates that co-incubation of MDA-MB-231 with HPMEC secrets CYR61 probably via the CYR61/integrin αvβ1 signaling pathway to promote adhesion-invasion of TNBC (early metastatic step). Metapristone, by interfering the adhesion-invasion process, prevents metastasis from happening.